  home solving equations with fractions methods for solving quadratic equations solving equations solving equations linear equations solving equations solving equations with variables on each side solving equations linear equations solving linear equations steps for solving linear equations solving equations with variables on each side solving quadratic equations solving equations solving equations steps for solving linear equations quadratic equations writing linear equations solving equations solving rational equations solving equations solving equations solving systems of equations using elimination solving linear equations solving equations solving quadratic equations methods for solving quadratic equations solving equations solving equations equation solving resources
Try the Free Math Solver or Scroll down to Tutorials!

 Depdendent Variable

 Number of equations to solve: 23456789
 Equ. #1:
 Equ. #2:

 Equ. #3:

 Equ. #4:

 Equ. #5:

 Equ. #6:

 Equ. #7:

 Equ. #8:

 Equ. #9:

 Solve for:

 Dependent Variable

 Number of inequalities to solve: 23456789
 Ineq. #1:
 Ineq. #2:

 Ineq. #3:

 Ineq. #4:

 Ineq. #5:

 Ineq. #6:

 Ineq. #7:

 Ineq. #8:

 Ineq. #9:

 Solve for:

 Please use this form if you would like to have this math solver on your website, free of charge. Name: Email: Your Website: Msg:

Factorizing a quadratic expression and finding the roots of a quadraticequation are closely related.

Example 1

Find the solution to the equations

(a) x + 6cx + 8 = 0, (b) x - 4x + 4 = 0.

Solution

(a) The quadratic expression will factorize as follows.

x + 6x + 8 = (x + 2)(x + 4).

The solution to the equation may now be obtained;

If x + 6x + 8 = 0

then (x + 2)(x + 4) = 0 .

Thus either (x + 2) = 0, or (x + 4) = 0. The solution to the equation is thus x = -2 or x = -4.

(b) In this example the expression is

x - 4x + 4 = (x - 2)(x - 2) = (x - 2) .

The solution to the equation x - 4x + 4 = 0 is thus x = 2.

In this case, the equation is said to have equal roots.

Exercise 1

Find the solution to each of the following equations.

(a) 2x + 5x + 3 = 0

(b) 3x + 7x + 2 = 0

(c) 3y - 5y - 2 = 0

(d) 4z - 23z + 15 = 0

(e) 64z + 4z - 3 = 0

(f) 4w - 25 = 0

Solution

(a) We can easily see that

2x + 5x + 3 = (2x + 3)(x + 1) .

Thus if 2x + 5x + 3 = 0 then we have

either (2x + 3) = 0 , or (x + 1) = 0.

For the first of these

2x + 3 = 0

2x = -3 (adding -3 to both sides) (dividing both sides by 2) .

The solution to the second is obviously x = -1.

(b) We can easily see that

3x + 7x + 2 = (3x + 1)(x + 2) ,

so that if 3x + 7x + 2 = 0 ,

then (3x + 1)(x + 2) = 0 .

Thus either 3x + 1 = 0 or x + 2 = 0 .

For the first of these 3x + 1 = 0

3x = -1 (adding -1 to both sides) (dividing both sides by 3) .

The solution to the second part is obviously x = -2. The solution to the original equation is thus x = -2 or x = -1/3.

(c) We can easily see that

3y - 5y - 2 = (3y + 1)(y - 2) = 0 .

Thus either 3y + 1 = 0, or y - 2 = 0. For the first part,

3y + 1 = 0 ,

3y = -1 (adding -1 to both sides) , (dividing both sides by 3) .

The solution to the second part is obviously y = 2.

The quadratic equation 3y - 5y - 2 = 0 thus has the solution y = -1/3 or y = 2.

(d) We can easily see that

4z - 23z + 15 = (4z - 3)(z - 5) = 0 .

Thus either 4z - 3 = 0, or z - 5 = 0.

Proceeding as in the previous examples, the solution to the first partis z = 3/4 and to the second part is z = 3.

The solution to 4z - 23z + 15 = 0 is therefore z = 3/4 or z = 3.

(e) We can easily see that

64z + 4z - 3 = (16z - 3)(4z + 1) = 0 .

Thus either 16z - 3 = 0 or 4z + 1 = 0. For the first part

16z - 3 = 0 ,

16z = 3 (adding 3 to both sides) , (dividing both sides by 16) .

For the second part 4z + 1 = 0

4z = -1 (adding -1 to both sides) ,

z = -14 (dividing both sides by 4) .

The solution to the equation 64z + 4z - 3 = 0 is thus z = 3/16 or z = -1/4.

(f) We can easily see that

4w - 25 = (2w - 5)(2w + 5) = 0.

The solution to this is w = 5/2 or w = -5/2 , i.e. w = ±5/2 .

Quiz

Which of the following is the solution to the quadratic equation 12x + 17x - 14 = 0 ?

(a) 2, 7/12 (b) -2, -7/12 (c) -2, 7/12 (d) 2, -7/12

Solution

This quadratic is the one that occurs in the first quiz. There it was seen that 12x + 17x - 14 = (x + 2)(12x - 7), so

either x + 2 = 0 or 12x - 7 = 0 .

The solution to the first is x = -2 and to the second is x = 7/12.